Comparing Item Performance on Three- Versus Four-Option Multiple Choice Questions in a Veterinary Toxicology Course - Kenneth Royal; David Dorman (Veterinary Sciences, 2018)
Background: The number of answer options is an important element of multiple-choice questions (MCQs). Many MCQs contain four or more options despite the limited literature suggesting that there is little to no benefit beyond three options. The purpose of this study was to evaluate item performance on 3-option versus 4-option MCQs used in a core curriculum course in veterinary toxicology at a large veterinary medical school in the United States. Methods: A quasi-experimental, crossover design was used in which students in each class were randomly assigned to take one of two versions (A or B) of two major exams. Results: Both the 3-option and 4-option MCQs resulted in similar psychometric properties. Conclusion: The findings of our study support earlier research in other medical disciplines and settings that likewise concluded there was no significant change in the psychometric properties of three option MCQs when compared to the traditional MCQs with four or more options.